ACGH Analysis of Predictive Biomarkers for Response to Bevacizumab plus Oxaliplatin‐ or Irinotecan‐Based Chemotherapy in Patients with Metastatic Colorectal Cancer. (13th November 2018) - Fujita, Yoshihiko; Taguri, Masataka; Yamazaki, Kentaro; Tsurutani, Junji; Sakai, Kazuko; Tsushima, Takahiro; Nagase, Michitaka; Tamagawa, Hiroshi; Ueda, Shinya; Tamura, Takao; Tsuji, Yasushi; Murata, Kohei; et al.
Abstract: Background: The randomized phase III study (WJOG4407G) showed equivalent efficacy between FOLFOX and FOLFIRI in combination with bevacizumab as the first‐line treatment for metastatic colorectal cancer (mCRC). We studied whole genome copy number profiles using array‐based comparative genomic hybridization (aCGH) analysis of tumor tissue samples obtained in this study. The aim of this study was to identify gene copy number alterations that could aid in selecting either FOLFOX or FOLFIRI in combination with bevacizumab for patients with mCRC. Materials and Methods: DNA was purified from 154 pretreatment formalin‐fixed paraffin‐embedded tissue samples (75 from the FOLFOX arm and 79 from the FOLFIRI arm) of 395 patients enrolled in the WJOG4407G trial and analyzed by aCGH. Genomic regions greater than 1.2‐fold were regarded as copy number gain (CNG). Results: Patient characteristics between the treatment arms were well balanced except for tumor laterality (left side; 64% in FOLFOX arm and 80% in FOLFIRI arm, p = .07). FOLFIRI showed a trend toward better response rate (RR), progression‐free survival (PFS) and overall survival (OS) than FOLFOX in the patients with CNG of chromosome 8q24.1 (Fisher's exact test, p = .134 for RR; interaction test, p = .102 for PFS and p = .003 for OS) and 8q24.2 (Fisher's exact test, p = .179 for RR; interaction test, p = .144 for PFS and p = .002 for OS). Conclusion: Chromosome 8q24.1–q24.2 may contain genes that could potentially serve as predictive markers for selecting either FOLFOX or FOLFIRI in combination with bevacizumab for treatment of patients with mCRC. Implications for Practice: Bevacizumab has been used as a standard first‐line treatment for patients with metastatic colorectal cancer (mCRC) in combination with either oxaliplatin‐based or irinotecan‐based chemotherapy. Until now, there has been no predictive marker to choose between the two combination chemotherapies. This array‐based comparative genomic hybridization analysis revealed that the difference in therapeutic effect between the two combination chemotherapies is prominent in patients with mCRC with gene copy number gain in chromosome 8p24.1–p24.2. Such patients showed more favorable response and survival when treated with irinotecan‐based combination chemotherapy. Overlapping genes commonly found in this region may be predictive biomarkers of the efficacy of the combination chemotherapy with bevacizumab. Abstract : This article reports gene copy number alterations that could aid in selecting either FOLFOX or FOLFIRI in combination with bevacizumab for patients with metastatic colorectal cancer.